2007
DOI: 10.1124/dmd.107.018051
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Hepatic Drug-Metabolizing Enzyme Genes by Toll-Like Receptor 4 Signaling Is Independent of Toll-Interleukin 1 Receptor Domain-Containing Adaptor Protein

Abstract: ABSTRACT:During inflammation, drug metabolism and clearance are altered due to suppression of hepatic drug-metabolizing enzyme (DME) genes and their regulatory nuclear receptors (NRs) [pregnane X receptor, constitutive androstane receptor, and retinoid X receptor ␣ (RXR␣)]. The bacterial endotoxin, lipopolysaccharide (LPS), induces expression of proinflammatory cytokines in the liver, which contribute to altered DME expression. LPS binds to the cell-surface receptor, Toll-like receptor 4 (TLR4), which initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 39 publications
2
55
1
Order By: Relevance
“…Role of CAR in Regulation of DME Genes through TLR2 and TLR4 177 at ASPET Journals on May 12, 2018 dmd.aspetjournals.org Downloaded from CAR gene expression (;70%) at 16 hours (Ghose et al, 2008(Ghose et al, , 2009. LTA administration led to downregulation of Cyp3a11, Cyp2a4, Cyp2b10, Ugt1a1, Sultn, and Mrp2 genes in CAR +/+ mice at time points ranging from 4 to 16 hours, as we have seen previously (Ghose et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Role of CAR in Regulation of DME Genes through TLR2 and TLR4 177 at ASPET Journals on May 12, 2018 dmd.aspetjournals.org Downloaded from CAR gene expression (;70%) at 16 hours (Ghose et al, 2008(Ghose et al, , 2009. LTA administration led to downregulation of Cyp3a11, Cyp2a4, Cyp2b10, Ugt1a1, Sultn, and Mrp2 genes in CAR +/+ mice at time points ranging from 4 to 16 hours, as we have seen previously (Ghose et al, 2009).…”
Section: Discussionsupporting
confidence: 49%
“…Several studies have shown that downregulation of PXR and CAR genes was associated with decreased DME and transporter gene expression (Beigneux et al, 2000(Beigneux et al, , 2002Ghose et al, 2004Ghose et al, , 2008Ghose et al, , 2009. We have also shown that there is preferential suppression of CAR and its target hepatic genes on administration of LTA (Ghose et al, 2009).…”
Section: Introductionmentioning
confidence: 49%
See 2 more Smart Citations
“…Because of the unique anatomical link between the liver and intestines, Kupffer cells encounter high levels of gut-derived toxins (Su, 2002;Seki and Brenner, 2008). We have previously shown that TIRAP was also not involved in TLR4-mediated induction of hepatic cytokines (Ghose et al, 2008). These results indicate that Kupffer cells may not require TIRAP to recruit MyD88 to initiate signaling, whereas hepatocytes may require TIRAP to recruit MyD88.…”
Section: Tlr2 and Tirap In Regulation Of Hepatic Dme Gene Expressionmentioning
confidence: 48%